Various structures of complexes fabricated using transition metals and triazole ligands and their inhibition effects on xanthine luminescence. (11th August 2016) - Shang, Di; Ni, Juechen; Gao, Xinyu; Li, Chengren; Lin, Xiaomeng; Wang, Zhinan; Du, Ning; Li, Shuang; Xing, Yongheng
Abstract : The interaction between novel transition metal complexes and xanthine luminescence was studied for the first time. Abstract : Self-assembled mono- and bi-nuclear complexes of Cd(ii ) (1 ), Co(ii ) (2 ), Zn(ii ) (3 ), Ni(ii ) (4 ) and Cu(ii ) (5 ) were synthesized via the reaction of 5-methyl-1-(4-carboxylphenyl)-1 H -1, 2, 3-triazole-4-carboxylic acid (H2 L) and the corresponding metal salt under hydrothermal conditions. All complexes were characterized using elemental analysis, IR spectroscopy, UV-vis spectroscopy, PXRD analysis, thermogravimetry and single-crystal X-ray diffraction. Structural analyses show that the H2 L ligand exhibits diverse coordination modes: μ2 -η 1 O -η 1 O -η 1 O -η 1 N for1, μ2 -η 1 O -η 1 O -η 1 N for2–4 and μ3 -η 1 O -η 1 O -η 1 N -η 1 O for5 . Based on the various structures and the luminescent response of xanthine (3, 7-dihydro-purine-2, 6-dione), a new experiment for exploring the interaction between transition metal complexes and luminescent xanthine was performed for the first time. The results show that the luminescence response of xanthine depends on the concentration of metal complex.